2008
DOI: 10.1016/j.freeradbiomed.2008.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Role and regulation of ferritin H in rotenone-mediated mitochondrial oxidative stress

Abstract: Tight regulation of intracellular iron levels in response to mitochondrial dysfunction is an important mechanism that prevents oxidative stress, thereby limiting cellular damage. Here, we describe a cytoprotective response involving transcriptional activation of the ferritin H gene in response to the mitochondrial complex I inhibitor and neurotoxic compound, rotenone. Rotenone exposure increased ferritin H mRNA and protein synthesis in NIH3T3 fibroblasts and SH-SY5Y neuroblastoma cells. Transient transfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 47 publications
(65 reference statements)
1
27
0
Order By: Relevance
“…Also oxidative stress induced a significant increase (up to 80 fold) in ferritin mRNA (Torti and Torti 2002;Hintze and Theil 2005). A combination of different repressor (Bach1 and ATF1) (Iwasaki et al 2007;Hintze et al 2007) and activators (Nrf2, JunD) (Iwasaki et al 2006;MacKenzie et al 2008) are involved in the recognition and binding of the Antioxidant Response Elements (ARE) in the promoter region of mouse ferritin H and L genes, modulating their expression in response to oxidative stimuli. Different signaling cascades may enroll such DNA binding factors; for instance, the activation of PI3-kinase was required for ferritin H induction by oxidative agents in Jurkat cells (Sakamoto et al 2009); in the same cell type resveratrol, a molecule with antioxidant properties, induced ferritin H transcription via the recruitment of AMP-activated kinase (Iwasaki et al 2013).…”
Section: Regulation Of Ferritin Expressionmentioning
confidence: 99%
“…Also oxidative stress induced a significant increase (up to 80 fold) in ferritin mRNA (Torti and Torti 2002;Hintze and Theil 2005). A combination of different repressor (Bach1 and ATF1) (Iwasaki et al 2007;Hintze et al 2007) and activators (Nrf2, JunD) (Iwasaki et al 2006;MacKenzie et al 2008) are involved in the recognition and binding of the Antioxidant Response Elements (ARE) in the promoter region of mouse ferritin H and L genes, modulating their expression in response to oxidative stimuli. Different signaling cascades may enroll such DNA binding factors; for instance, the activation of PI3-kinase was required for ferritin H induction by oxidative agents in Jurkat cells (Sakamoto et al 2009); in the same cell type resveratrol, a molecule with antioxidant properties, induced ferritin H transcription via the recruitment of AMP-activated kinase (Iwasaki et al 2013).…”
Section: Regulation Of Ferritin Expressionmentioning
confidence: 99%
“…We demonstrated that both mouse and human ferritin H genes are transcriptionally activated under oxidative stress via a well-conserved far-upstream enhancer element, antioxidant-responsive element (ARE) (Iwasaki et al, 2006;Tsuji, 2005;Tsuji et al, 1995;Tsuji et al, 2000). The induction of ferritin during oxidative stress is an important cell defence mechanism against oxidative cell damage (Kaur et al, 2003;MacKenzie et al, 2008b;Pham et al, 2004;Sakamoto et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This argues strongly for the integration of Fe metabolic adaptation as an intrinsic component of inflammation and immunity, presumably contributing to host protection against infection (46,116). FTH transcription is also regulated by the transcription factor NRF2 (112,129), suggesting yet another level of integration between cellular adaptation to oxidative stress and Fe metabolic adaptation during infection. The transcription factor hypoxia-inducible factor alpha and heat shock factor 1 also regulate FTH expression in Caenorhabditis elegans (2), arguing for yet a broader level of integration between Fe metabolic adaptation and cellular responses to different forms of stress associated with inflammation and immunity.…”
Section: Fth and Infectionmentioning
confidence: 99%